Health-related quality of life, continuity of care and patient satisfaction: long-term outcomes of former patients of the Tuebingen Transition Program (TTP) - a retrospective cohort study - Luca Samuel Boeker; Jasmin Beate Kuemmerle-Deschner; Sebastian Jonas Saur; Jens Klotsche; Gabriele Erbis; Sandra Hansmann (BMC, 2022)
Abstract Background A significant number of patients in pediatric rheumatology suffer from ongoing disease activity into adulthood and thus need to be transferred into adult care. Transition as a structured individual process of preparation and patient empowerment can reduce risks of adverse long-term outcomes. The aim of this study was to measure long-term transition outcomes such as health-related quality of life (HR-QoL), patient satisfaction, and continuity of care in former patients of the interdisciplinary Tuebingen Transition Program (TTP). Methods In an iterative team process, a standardized questionnaire was developed including the EQ-5D-5L to measure HR-QoL, visual analogue scales to measure various items of patient satisfaction, further questions on continuity of care and physical activity and physician global assessment (PGA) to determine disease activity. HR-QoL and physical activity were compared to data from the average German population. Data was analyzed descriptively, and a logistic regression analysis was performed to identify possible predictive factors for negative outcomes. Results Response rate was 28.8% (85/295), 70.6% were female and median age was 24.1 years. 70.6% were diagnosed with juvenile idiopathic arthritis (JIA). Overall, HR-QoL was high (79.8 on the EQ VAS), yet lower than in the average population. The study cohort was more physically active than the respective average age groups. Mean patient satisfaction with pediatric care (8.4; standard deviation (SD) 1.7) and with the transition program (7.9; SD 2.6) was higher than with adult care (7.7; SD 2.2). 76.5% of participants received regular rheumatologic care after transfer. After excluding all participants in remission, the drop-out rate was 4.7%. A low PGA at the time of transfer was associated with higher HR-QoL and patient satisfaction after transfer. Conclusions HR-QoL of adult patients after successful transfer to adult rheumatology is reduced compared to the general population but physical activity and achievement of clinical remission could help to prevent negative long-term outcomes. Patient satisfaction and self-management of TTP patients were generally high, whereas youth-specific issues and their impact on the disease mandate greater attention. Treatment discontinuation rates were low and mostly due to remission. Further studies should focus on the identification of early predictors of long-term outcome to improve the process and outcome of transition.